2001
DOI: 10.1159/000050153
|View full text |Cite
|
Sign up to set email alerts
|

Single and Multiple Pyogenic Liver Abscesses: Etiology, Clinical Course, and Outcome

Abstract: Background: Pyogenic liver abscesses are uncommon but they still carry a high mortality rate when encountered. This study was undertaken to evaluate the differences in the clinical behaviour of patients with single and multiple abscesses. Methods: From January 1985 to December 1997, 133 patients with this disease were treated in the surgical departments of five hospitals, 97 had a single abscess and 36 had multiple abscesses. Clinical features, methods of treatment, and outcome were assessed and compared in bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
22
3
14

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(45 citation statements)
references
References 13 publications
4
22
3
14
Order By: Relevance
“…This is consistent with the fact that every recurrence was ipsilateral to the first event. Mortality in our series was 7.8%, similar to that reported in the 16,17,22,27,28 studies have analyzed risk factors for mortality, including the presence of active oncologic 17,22,26,29,30 renal failure, 17,18,22,26,29 hiperbilirrubinemia, 17,29,30 hypoalbuminemia, 17,29 MDRB isolation 17,29 and multiple abscesses 17,22,26,29,30 with inconsistent results. In our series, factors associated with mortality in univariate analysis included biliary disease, multiple abscesses, the bilateral liver involvement, and bilirrubinemia >5 mg/dL.…”
Section: Discussionsupporting
confidence: 85%
“…This is consistent with the fact that every recurrence was ipsilateral to the first event. Mortality in our series was 7.8%, similar to that reported in the 16,17,22,27,28 studies have analyzed risk factors for mortality, including the presence of active oncologic 17,22,26,29,30 renal failure, 17,18,22,26,29 hiperbilirrubinemia, 17,29,30 hypoalbuminemia, 17,29 MDRB isolation 17,29 and multiple abscesses 17,22,26,29,30 with inconsistent results. In our series, factors associated with mortality in univariate analysis included biliary disease, multiple abscesses, the bilateral liver involvement, and bilirrubinemia >5 mg/dL.…”
Section: Discussionsupporting
confidence: 85%
“…Half of the pyogenic liver abscesses are multicentric and three-fourth are located on right lobe. In this study, 77% lesions are located on right side which is in accordance with similar results from Alvarez et al 15 and Wong et al 16 . Regarding multicentricity, one third of patients in this study had multiple lesions, as also reported by other studies 9,11 .…”
Section: Discussionsupporting
confidence: 93%
“…USG is usually the initial study of choice with reported sensitivity of 83% to 95% for diagnosis of PLA. 11,12 A mature abscess with pus has distinct wall and become hypoechoic. 13 CT scan is highly sensitive in detecting small PLA.…”
Section: Introductionmentioning
confidence: 99%